REGULATORY CHALLENGES OF THE DIGITAL ECONOMY: INTERNATIONAL APPROACHES TO STANDARDIZING ACCOUNTING, AUDITING AND FINANCIAL REPORTING (Ustozlar uchun, 2025)
The rapid development of the digital economy has significantly transformed accounting, auditing, and financial reporting processes across the globe. Digital technologies—such as artificial intelligence, blockchain, cloud computing, big data analytics, and digital payment systems—have introduced both opportunities and regulatory challenges for financial information systems. While these technologies enhance transparency, efficiency, and accuracy, they also create complexities in ensuring compliance with international standards such as IFRS, ISA, and global regulatory frameworks. This paper examines major regulatory challenges arising from digitalization and evaluates international approaches to harmonizing accounting, auditing, and financial reporting standards. The study highlights the need for unified digital regulations, enhanced cybersecurity frameworks, cross-border cooperation, and capacity-building initiatives to ensure the integrity and reliability of financial information in the digital era.